Use of Suweg (Amorphopallus campanulatus )Tuber Flour Substitute bread flour on the quality of sweet bread - Ketaren, Bunga Raya; Rangkuti, Bella Triana; Ardilla, Desi; Novita, Aisar (Talenta Publisher, 2022)
Healthy food is food that is rich in fiber, therefore this study was conducted to see the difference in the making of sweet bread by substituting wheat flour to Suweg tuber flour which is believed to be higher in fiber and better, besides that the treatment is to add CMC concentration in the manufacture of sweet bread. The Objective of this study was to obtain the best substitution effect of wheat flour and Suweg tuber flour in terms of nutritional value and quality of sweet bread and to determine the effect of CMC concentration in the manufacture of sweet bread. This study used a completely randomized design (CRD) method with two factorials. Factor I is the ratio of wheat flour and flour (T) consisting of 5 levels, namely T0 = 200: 0, T1 = 180: 20, T2 = 160: 30, T3 = 140: 60, T4 = 120: 80. Factor II is CMC concentration (C) consists of 3 levels, C1 = 0.37, C2 = 0.75, C3 = 1.12. Observational parameter tests carried out were color organoleptic tests, texture organoleptic tests, flavour organoleptic tests, taste organoleptic tests, expansion volume, water content, ash content, fat content, fiber content, and protein content. The results showed that the ratio of wheat flour and Suweg tuber flour had a very significant difference (p<0.01) on color organoleptic, flavour organoleptic, texture organoleptic, taste organoleptic, dough volume expansion, moisture content, content fat content, protein content and crude fiber content, while the concentration of CMC was very significant (p<0.01) on color organoleptic, texture organoleptic, dough volume expansion organoleptic, water content, protein content, fat content, and crude fiber content.